Verbalization of an Informing Communication Strategy in Consulting Cancer Patients - V. O. Fedorovskaya; T. A. Osipenko (Научный диалог)
The article is devoted to the problem of communicative interaction in the “doctor — patient” dyad. The relevance of the study is due to the need to return the humanistic principle to medical practice and to increase the efficiency of communication between medical personnel and patients, both in their native language and in a foreign language. The aim of the study is to identify the means of verbalization of the informing communicative strategy, which the doctor uses during a consultation of cancer patients. The empirical material was authentic consultative conversations in German, recorded in the GAT-2 transcription system. It has been proven that in the material under study, the informative communicative strategy is dominant. Six main tactics of the informing strategy have been identified: the tactics of explanation, the tactics of planning, the tactics of recommending therapy, the tactics of updating the medical history, the tactics of communicating the diagnosis, and the tactics of checking the contact. Special attention is paid to the distinctive features of the structure of the dialogues under consideration and their influence on the sequence of reproduction of the selected tactics. Frequent language means of implementing tactics, as well as the explicit and implicit goals of their use, are systematized. It is concluded that the use of communicative tactics corresponds to the specifics of the patient-centered approach.